The Growth Pattern and Potential Development of Manufacturing Industry in East Java - Ida Nuraini; Arfida Boedi Rochminarni; Happy Febrina Hariyani (Universitas Muhammadiyah Ponorogo, 2021)
The manufacturing industry in East Java has an important role in supporting the economy so that its development must be evenly distributed throughout all districts and cities. This research aims to: 1) measuring the performance of the manufacturing industry, 2) mapping the growth patterns of the manufacturing industry, 3) describing which district/cities in East Java have the potential to be developed and 4) knowing which variables determine the performance of the manufacturing industry. The research objects are 9 cities and 29 districts. The data used is secondary data sourced from the Central Statistics Agency. The data is processed by sharing output contribution analysis, labor absorption contribution, Klassen typology analysis and panel data regression analysis. The results showed that the performance of the industrial sector was very low and uneven between regions, the rate of employment in the industrial sector was also low in all regions. The growth pattern of the industrial sector in 22 districts/cities in the Relatively Underdeveloped classification and 15 districts/cities in the Potential classification and 1 district in the Forward Depressed classification. Inflation variables and the number of business units have a significant effect on industry performance. For this reason, it is recommended that local governments be able to control the inflation rate and be able to provide stimulus or policies to the industrial sector in order to increase productivity and performance.